Evaluating function in the hallux valgus foot following a 12-week minimalist footwear intervention: A pilot computational analysis. (February 2022) - Xiang, Liangliang; Mei, Qichang; Wang, Alan; Shim, Vickie; Fernandez, Justin; Gu, Yaodong
Abstract: Hallux valgus is a foot pathological condition showing a lateral deviation of the first phalange and medial deviation of the first metatarsal. The purpose of the current study was to evaluate a longitudinal effect of minimalist footwear running protocol for a mild/moderate hallux valgus patient. The computer tomography (CT) images from a male hallux valgus (HV) patient were respectively scanned pre and post 12-week minimalist footwear running intervention. The pre and post -intervention foot finite element (FE) models were developed from the foot three-dimensional geometries manually segmented via the MIMICS 21.0. The post-process with SolidWorks 2019 was conducted for model assembly, consisting of 24 bones, 22 cartilages, five plantar fascia, and lumped encapsulated soft tissue. The foot FE models were solved in ANSYS Workbench 2020 R1 package. The FE models were validated against the plantar pressure (pre : 0.146 MPa vs 0.155 MPa, and post : 0.156 MPa vs 0.17 MPa) and vertical displacements (pre : 2.6 mm vs 2.4 ± 0.4 mm, and post 1.1 mm vs 1.3 ± 0.4 mm) of navicular measured from experiments. The first metatarsophalangeal joint showed varus realignment and the von Mises stress in the first metatarsal and the second metatarsal decreased 72.1% and 51.2% compared with pre-intervention (M1: 4.41 MPa and M2: 4.18 MPa). This framework investigated the shape adjustment and functional recovery in the mild/moderate HV deformity, which may provide references and implications for future studies with a larger cohort.